Remediation of Tri-butyltin (TBT) and Heavy Metal Contaminated Sludge by Freezing/thawing Method - Shekarrizfard, Mahshid (2012)
Concentrations of Tin-organic compounds have been found in marine and in harbor sediments. TBT was used for panting boats and ships. The other degradation products which are coming with TBT are dibutyltin (DBT) and monobutyltin (MBT), etc. In the 1970’s, it was diagnosed that tin-organic compounds are harmful organic compounds to the chemical and biological processes in an environment. Tin-organic compounds have a strong bond to the suspended material and organic material sediments. It can precipitate into the different levels of sea and stream. The TBT has entered to the food chains, and is found in a human skin and hair follicles. Tin-organic compounds were found in the Pacific Oyster that showed an increase in the endogenous testosterone level. Thus it caused by, the toxicity properties of paint degradation product in the coastal areas. Many methods that were utilized for treat the wastewater from industrial operations includes; physical, chemical and biological methods. Many methods were used for remediation of the TBT contamination, such as implantation of a salt marsh plants and bioremediation technique. The physical techniques, such as electrical and thermal treatment were also used. Due to the concentration of TBT and heavy metals in the water close to floc particles, the freezing/thawing method may has shown to be a beneficial way to treat contamination in sediment or sludge, although it has a high treatment cost. The freezing /thawing method has a high treatment cost compared to other techniques. In the freezing process the water around particles has been frozen and it can be drainage by thaw/leached steps. This method has the possibility to separate a colloidal particle from the liquid phases to the wastewater sludge. In the freezing steps the pore water starts to freeze in the middle of the pore, and leaving areas of unfrozen water that it is closed to the surface particles. By a fast freezing rate, the surface water cannot be extracted by thawing steps. But when the freezing rate is slowed down with ...